Analisis Hukum Terhadap Pengenaan Pajak Ganda - Wirawan B. Ilyas (Fakultas Hukum Universitas Islam Indonesia, 2012)
This research focused on the aspects of inequality and legal uncertainty due to the double taxation (double taxation) on the same object. As a result, the tax burden felt by the public will feel heavy. The research also examines the Constitutional Court ruling on the petition for the perceived tax law has imposed double taxation on an object the same tax. Analysis of the research done by looking at the tax benefit that should be used for national interests rather than the interests that are regional (sectoral) because of the potential tax on an area. Moreover, coordination among government agencies that are not effectively be an additional analysis to be more comprehensive in its discussion.